Editorial Note DAC 5.2 - Ana Rainha; Varzim Miranda, Marta; Azevedo, Margarida; Lemos, João (Design/Arts/Culture, 2026)
In the second issue, entitled ‘Polarities, limits and thresholds,’ the tensions observed in vol. 1 are revisited, identified there as axes of problematisation in contemporary debate. If, as we have seen, extreme positions have intensified conflicts and discourses of exclusion, weakening the common space and deepening social and political fragmentation, on the other hand, problematising the figures of the limit and the threshold can constitute other modes of collective mobilisation and critical reflection. Assuming this dynamic as a condition for recognising cultural and social differences, rethinking public and media space, and reorganising human and technological connections, rather than trying to resolve them categorically, allows us to configure new forms of relationship, thought, and representation. Therefore, this new issue of the publication highlights educational projects and institutional collaboration protocols, research issues, as well as considerations and processes noted in the fields of art and design that rearticulate this condition. Guest Editors: Ana Rainha; João Lemos; Margarida Azevedo; Marta Varzim Miranda Editorial Note: Ana Rainha, Margarida Azevedo, Marta Varzim Miranda, João Lemos. Contributions to this issue include: Eleana Stoikou; José Simões; Ricardo Bonacho; Olga Noronha; Helena Cordeiro; Ana Duque; Efstratios Pantazis; Miguel Vidal; Alexandre Almeida; Renato Seixas; María Gárgoles Navas; Tomé Saldanha Quadros; Joana Pinto; José Saraiva. Graphic Design: João Lemos, Margarida Azevedo